DaF-Grammatikerwerb bei italophonen Lernenden. Erwerbsphasen, Lernstrategien und didaktische Implikationen - Ballestracci, Sabrina (Kritik. Rivista di letteratura e critica culturale, 2023)
An L2 teacher must certainly possess a good knowledge of the second language he/she wishes to teach (e.g. speaking, writing, grammar and culture). However, the knowledge of the learning difficulties or the strategies emerging in the L2 acquisition process are also remarkably important, if not indispensable. This paper intends both to offer some notions and reflexions on this subject and to focus on the acquisition of L2 German grammar in guided context, trying to build a bridge between theory, empirical research, and teaching praxis. The aim is to propose teaching practices based on the factual acquisition difficulties of Italian learners of L2 German. The work consists essentially of three parts. The first part, a theoretical one, introduces the main definitions of acquisition (Chapter 1), and describes the most important theoretical approaches existing in the field of language acquisition (Chapter 2). Chapter 3 focuses on the acquisition of L2 German, with particular attention for L1 Italian learners and for the different acquisition strategies identifiable in each phase of the L2 acquisition process: chunks, simplifications, generalizations, interferences from L1 and from other L2 languages and intralingual interferences. Chapter 4 reflects on didactical implications which can be formulated on the basis of the empirical data; it also gives suggestions for the teaching of L2 German.